Investigation the effect of dopant Te on CdSe thin films deposited by RF magnetron sputtering method. (1st May 2023) - Kumar, Devendra; Lal, Chiranji; Veer, Dharm; Singh, Deshraj; Kumar, Pawan; Katiyar, Ram S
Abstract: CdSe and CdSe:Te thin films were grown on glass substrates by RF magnetron sputtering. The doping percentage of Tellurium (Te) in CdSe was 7% for the CdSe:Te thin film. The microscopic images of the films were found to be uniform and homogeneous in nature with a uniform grain and no cracks, and the grain size of CdSe was higher than CdSe:Te thin film. CdSe:Te thin film shows a higher absorption coefficient compared to CdSe in the visible region. The Energy band gaps were found to be 2.01 and 1.73 eV for CdSe and CdSe:Te thin films, respectively. The incorporation of Te atom into the CdSe structure has enhanced the mobility and changed the type of conductivity from n-type to p-type.